Online social support for complex regional pain syndrome - Smedley, Richard (2016)
Individuals living with Complex Regional Pain Syndrome (CRPS) often experience difficulties taking part in social and recreational activities, which can leave them with a greatly reduced social network and limited opportunities for obtaining social support. Online support communities may provide individuals with an alternative way of obtaining social support, but few studies have examined these communities in the context of CRPS. Furthermore, most online support community research has focussed on established communities, and little is known about how new communities become established. This thesis examines a bespoke CRPS online support community with two broad aims: to examine the development of online support processes in relation to the launch of a new online support community, and to investigate the provision of social support for CRPS within an online support community. The dataset comprised 221 messages posted by 23 participants. Study 1 used the full dataset to examine engagement with the online support community, focussing on the number of individuals who used the forum (membership growth), how they used it (header analysis) and how they introduced themselves (introductory messages). Study 2 used the full dataset to investigate how support processes became established, the support content of messages, and how this contributed to the CRPS ‘four pillars of intervention’. Study 3 used four longitudinal case studies from the dataset to conduct a linguistic analysis of messages, focussing on support providing behaviour and the number of replies received. The results indicate that support processes start almost immediately when a new online support community is launched, and membership growth is closely linked to promotional strategies. Online support may play an important role in CRPS self-management by contributing to the ‘four pillars of intervention’, and there is a possibility that diffusion of responsibility may occur in forums. The longitudinal case study approach may produce important new insights and suggests that the use of health words is unrelated to the number of replies received, the use of self and other-oriented messages may be linked to health status and support providing activities, and that the ratio of positive-to-negative words could potentially be used to identify individuals who might benefit from additional support.